2020
DOI: 10.1002/aisy.201900189
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Metal‐Oxide Semiconductor and Memristive Hardware for Neuromorphic Computing

Abstract: The ever‐increasing processing power demands of digital computers cannot continue to be fulfilled indefinitely unless there is a paradigm shift in computing. Neuromorphic computing, which takes inspiration from the highly parallel, low‐power, high‐speed, and noise‐tolerant computing capabilities of the brain, may provide such a shift. Many researchers from across academia and industry have been studying materials, devices, circuits, and systems, to implement some of the functions of networks of neurons and syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(60 citation statements)
references
References 94 publications
0
60
0
Order By: Relevance
“…[ 134 ] Integration of CMOS and memristive technologies for neuromorphic applications is discussed in the previous study. [ 118 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 134 ] Integration of CMOS and memristive technologies for neuromorphic applications is discussed in the previous study. [ 118 ]…”
Section: Discussionmentioning
confidence: 99%
“…Given such energy concerns, systems based on low‐power memristive devices are a highly promising alternative. [ 117,118 ] Besides having a low carbon footprint, many studies demonstrated devices that mimic neurons, synapses, and plasticity phenomena. Often, such approaches work well for off‐line training.…”
Section: Future Of Neuromorphic and Bio‐inspired Computing Systemsmentioning
confidence: 99%
“…Consider, CMOS‐memristor hybrid hardware and artificial synapses are proposed to perform CNN and DNN operation. [ 182 ]…”
Section: Neuromorphic Computing Systems With Memristorsmentioning
confidence: 99%
“…In-memory computing (also called 'processing-in-memory') refers to any effort to process data at the residence of data (i.e., in the memory array) without moving it out to a separate processing unit. 'Processing/computing' could mean a wide variety of operations from arithmetic operations to cognitive tasks like machine learning and pattern recognition [23]. In this review, the focus is on arithmetic operations and how majority logic can enable efficient in-memory computing.…”
Section: Introductionmentioning
confidence: 99%